2022
DOI: 10.26905/enjourme.v7i1.7036
|View full text |Cite
|
Sign up to set email alerts
|

Using ADDIE model to develop learning materials of the test of English proficiency in Edmodo

Abstract: The preliminary analysis found that most of the students encountered several difficulties in achieving the target score of the Test of English Proficiency (TEP), such as low motivation and lack of vocabulary. Thus, this study attempts to develop the appropriate learning materials of the TEP preparation course for English Department students through Edmodo as the Learning Management System (LMS). Through the Research and Development method and employed the ADDIE model, 15 (fifteen) English Department students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Considering the numerous contributions that ADDIE provides in constructing the instructional tools as empirically explored by many scholars around the world, it revealed that the model helps teachers in many ways. In Indonesian context, it support teachers in evaluating the weakness and the strength points of a Course book (Iswati, 2019), preparing material in ICT based instruction, Edmodo, and putting students in positive environment throughout the TEP preparation class (Nita et al, 2022). The ADDIE model also address the problem of language skill material construction process, in Arab Gulf, the model barely supporting teacher in enhancing students' creative writing activates and selfconfidence (Almehli, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the numerous contributions that ADDIE provides in constructing the instructional tools as empirically explored by many scholars around the world, it revealed that the model helps teachers in many ways. In Indonesian context, it support teachers in evaluating the weakness and the strength points of a Course book (Iswati, 2019), preparing material in ICT based instruction, Edmodo, and putting students in positive environment throughout the TEP preparation class (Nita et al, 2022). The ADDIE model also address the problem of language skill material construction process, in Arab Gulf, the model barely supporting teacher in enhancing students' creative writing activates and selfconfidence (Almehli, 2021).…”
Section: Introductionmentioning
confidence: 99%